2012
DOI: 10.1155/2012/236807
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Signature Fatty Acid 16:1ω5 as a Tool to Determine the Distribution of Arbuscular Mycorrhizal Fungi in Soil

Abstract: Biomass estimation of arbuscular mycorrhiza (AM) fungi, widespread plant root symbionts, commonly employs lipid biomarkers, predominantly the fatty acid 16:1ω5. We briefly reviewed the application of this signature fatty acid, followed by a case study comparing biochemical markers with microscopic techniques in an arable soil following a change to AM non-host plants after 27 years of continuous host crops, that is, two successive cropping seasons with wheat followed by amaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 64 publications
0
52
1
Order By: Relevance
“…The sum of 18:2ω6,9, 18:3ω6, 18:3ω3 was used to represent total fungal PLFAs (Frostegård and Bååth 1996;Ruess and Chamberlain 2010). The NLFA 16:1ω5c was used as marker for arbuscular mycorrhizal fungi (AMF; nmol g −1 dry litter/soil material; Lekberg et al 2012;Ngosong et al 2012).…”
Section: Microorganismsmentioning
confidence: 99%
“…The sum of 18:2ω6,9, 18:3ω6, 18:3ω3 was used to represent total fungal PLFAs (Frostegård and Bååth 1996;Ruess and Chamberlain 2010). The NLFA 16:1ω5c was used as marker for arbuscular mycorrhizal fungi (AMF; nmol g −1 dry litter/soil material; Lekberg et al 2012;Ngosong et al 2012).…”
Section: Microorganismsmentioning
confidence: 99%
“…Nevertheless, based on the large number of studies in which typical higherplant-derived patterns of lipids are reported and used in soils (Table 1), including indicative ACL and CPI values, microbial input of longer chain length straight-chain lipids generally does not seem to be a major factor compared to directplant-derived input in the topsoil Bai et al, 2009). In contrast, for steroids and triterpenoids such as camposterol, stigmasterol, and lupeol, microbial input in soils can be considerable (Naafs et al, 2004a). As another example, arbuscular mycorrhizal fungi-derived β-sitosterol is by far the most abundant sterol identified in soils (Grandmougin-Ferjani et al, 1999).…”
Section: Microbial Inputmentioning
confidence: 99%
“…For instance, the oxidation of free fatty acids could be a source of ω-hydroxy fatty acids, whereas the microbial β-oxidation of unsaturated fatty acids and/or mid-chain hydroxy fatty acids may be a source of α-and ω-alkanediotic acids, thus clouding the cutin or suberin signal (Naafs et al, 2004b).…”
Section: Microbial Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLFA 16:1u5 has been proposed as a biomarker for AMF. However, it was not used here as it is also found in considerable quantities in Gram negative bacteria (Ngosong et al, 2012;Ruess and Chamberlain, 2010;Sharma and Buyer, 2015). Individual PLFA's were analysed for d 13 C using GC -combustionisotope ratio mass spectrometry (GC-C-IRMS) (Isoprime Ltd).…”
Section: -Plfa Analysesmentioning
confidence: 99%